The Influence Of Word Of Mouth And Distribution Channels On Consumer Purchasing Decisions For Seblak Crackers Products In PD. Kujang Jaya, Ciamis District - Nisa, Annida Bai'atun; Lestari, Suci Putri; Patimah, Titin (Universitas Dehasen Bengkulu, 2025)
This research aims to determine the influence of word of mouth and distribution channels on purchasing decisions for seblak cracker products in PD Kujang Jaya, Ciamis district. The method used in this research is causality through a survey approach, with the sample selected in this research being consumers of seblak crackers who are generally in Ciamis with a total of 100 respondents. The analytical tool used in this research is multiple linear regression using SPSS version 25. The research results show that simultaneously Word of Mouth and Distribution Channels have a significant effect on Purchasing Decisions. Partially, Word of Mouth has a negative and insignificant effect on purchasing decisions for seblak cracker products in PD Kujang Jaya, Ciamis district and the hypothesis is rejected. Meanwhile, partially the Distribution Channel has a positive and significant effect on purchasing decisions for seblak cracker products in PD Kujang Jaya, Ciamis district so that the hypothesis is accepted.